Efforts to increase dental and oral health knowledge for children at TPA Turi - Laelia Dwi Anggraini; Pandu Tri Atmojo; Zahra Fatia Diani; Safirah Putri Hidayati; Inayah Retno Cahayati; Fajriyah Khoiratunnisa; Gigih Ramadhan; Syauqi Ayasy Haidi; Athaya Intan Fitriani (Universitas Muhammadiyah Magelang, 2023)
Approximately 54% of children aged 5-9 years have cavities, damaged, or diseased teeth, yet only 14.6% of these children received treatment from medical dental personnel. This indicates a relatively low level of public awareness regarding general health, dental, and oral health. The objective of this program is to enhance knowledge of dental and oral health to prevent a rise in dental and oral problems in Indonesia. The community service employs an educational approach, covering both general and dental health. The program was conducted at TPA Turi, Sleman, and attended by 21 patients. The program results reveal that the majority of children and toddlers are healthy. Additionally, there was a 22.62% increase in knowledge about general health, dental, and oral health as a result of the program.